Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2019
DOI: 10.1186/s12935-019-0794-1
|View full text |Cite
|
Sign up to set email alerts
|

Silencing of SNHG6 induced cell autophagy by targeting miR-26a-5p/ULK1 signaling pathway in human osteosarcoma

Abstract: Background lncRNAs have been proved to play crucial parts in various human cytopathology and cell physiology, including tumorigenesis. Down-regulated lncRNAs SNHG6 have shown great cell proliferation inhibitory effects in cancer development. Here we investigated how SNHG6 effected human osteosarcoma (OS) development and progression. Methods: Reverse transcription-quantitative PCR was performed to detect SNHG6 mRNA level in both OS tissues and cell lines. MTT and colony formation assays were used t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
43
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 47 publications
(44 citation statements)
references
References 36 publications
1
43
0
Order By: Relevance
“…overexpressed SNHG6 reduces cell apoptosis but promotes cell cycle, cell migration, invasion, EMT, and chemoresistance. SNHG6 exerts its function mainly by serving as miRNA sponge to antagonize the connections between multiple tumor suppressor miRNAs and their target mRNAs [19][20][21][22][23] . In this study, we analyzed public database and found that SNHG6 was also upregulated in CCA cell lines and tissues, and functional investigations showed that SNHG6 silencing inhibited cell proliferation, migration, and HUVECs tube formation, which indicated that SNHG6 functioned as an oncogene in CCA.…”
Section: Discussionmentioning
confidence: 99%
“…overexpressed SNHG6 reduces cell apoptosis but promotes cell cycle, cell migration, invasion, EMT, and chemoresistance. SNHG6 exerts its function mainly by serving as miRNA sponge to antagonize the connections between multiple tumor suppressor miRNAs and their target mRNAs [19][20][21][22][23] . In this study, we analyzed public database and found that SNHG6 was also upregulated in CCA cell lines and tissues, and functional investigations showed that SNHG6 silencing inhibited cell proliferation, migration, and HUVECs tube formation, which indicated that SNHG6 functioned as an oncogene in CCA.…”
Section: Discussionmentioning
confidence: 99%
“…In recent years, studies have found that the abnormal expression of circular RNA (circRNA) is involved in the occurrence and development of a variety of tumors, and is expected to become a new target for tumor diagnosis and treatment. 4,5 CircRNA is a closed, circular non-coding RNA molecule formed by covalent bonding between the 3ʹ end and the 5ʹ end by reverse splicing. It is widely present in organisms and is more stable than linear RNA.…”
Section: Introductionmentioning
confidence: 99%
“…Sphingosine kinase 1 (SPHK1), as a cytosolic enzyme, maintains the intracellular sphingolipid balance and plays vital roles in cell growth, invasion, and autophagy. MicroRNA‐506‐3p initiates mesenchymal‐to‐epithelial transition and suppresses autophagy in osteosarcoma cells by directly targeting SPHK1 (Table ) …”
Section: Introductionmentioning
confidence: 99%
“…MicroRNA-506-3p initiates mesenchymal-toepithelial transition and suppresses autophagy in osteosarcoma cells by directly targeting SPHK1 (Table 1). 102…”
mentioning
confidence: 99%